Promoting Entrepreneurship in the Welfare State - Magnus Henrekson; Jesper Roine (The Research Institute of Industrial Economics (IUI), 2005)
Entrepreneurship is largely ignored or treated in a highly simplified way in endogenous growth theory. Still, it is now widely recognized that the supply of entrepreneurial talent is likely to be important for economic growth, innovation and job creation. In this study we provide an in-depth examination of how the supply of productive entrepreneurship is likely to be affected by the kind of tax and welfare arrangements that may prevail in a mature welfare state. Sweden, allegedly the most extensive of all welfare states, is the object of the empirical analysis. It is argued that the Swedish welfare state early on chose a specific Swedish Model of trying to combine ambitious welfare programs and a high tax burden with good opportunities for economic growth. This particular view rested heavily on the assumption that innovative activity was best performed in large established firms and that entry of new firms was less important. Consequently, policy and institutions were geared to promoting certain types of activities which could deliver growth if scale economies are important and intrapreneurship can substitute for entrepreneurship. However, in an environment where entry, exit and turnover of firms are important for growth, and where scale-economies are less important, this kind of model may be more problematic. Both aggregate economic performance and data on firm growth and direct measures of entrepreneurial activity are broadly consistent with the identified structure of payoffs. A number of measures that can be implemented to strengthen entrepreneurial incentives within extensive welfare states are discussed, but the fact still remains that an entrepreneurial culture and a welfare state are very remotely related. As a result, the respective cultures are unlikely to be promoted by a similar set of institutions.
Keywords: H30; J20; M13; O12; 330; Economic Growth; Entrepreneurship; Innovation; Swedish Model; Welfare State; Entrepreneurship-Ansatz; Sozialstaat; Wirtschaftswachstum; Innovation; Schweden